2007
DOI: 10.1126/science.1146317
|View full text |Cite
|
Sign up to set email alerts
|

TARP Auxiliary Subunits Switch AMPA Receptor Antagonists into Partial Agonists

Abstract: Quinoxalinedione compounds such as 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX) are the most commonly used alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor antagonists. However, we find that in the presence of transmembrane AMPA receptor regulatory proteins (TARPs), which are AMPA receptor auxiliary subunits, CNQX acts as a partial agonist. CNQX induced small depolarizing currents in neurons of the central nervous system, and reconstitution of this agonist activity required coexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
142
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(149 citation statements)
references
References 29 publications
6
142
0
Order By: Relevance
“…Rather, coexpression of CNIH2 and GluA1γ-8 results in channels exhibiting both deactivation kinetics consistent with CNIH association and kainate efficacy consistent with TARP association, demonstrating that these proteins can modulate AMPARs simultaneously. We further tested whether CNIH2 shares with TARPs the ability to convert the competitive antagonist CNQX into a partial agonist (18) and found that CNIH2 has no effect on the action of CNQX (Fig. S2C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, coexpression of CNIH2 and GluA1γ-8 results in channels exhibiting both deactivation kinetics consistent with CNIH association and kainate efficacy consistent with TARP association, demonstrating that these proteins can modulate AMPARs simultaneously. We further tested whether CNIH2 shares with TARPs the ability to convert the competitive antagonist CNQX into a partial agonist (18) and found that CNIH2 has no effect on the action of CNQX (Fig. S2C).…”
Section: Resultsmentioning
confidence: 99%
“…CNIH2 also increases AMPAR single channel conductance similarly to TARPs. However, CNIHs differ from TARPs in that they only minimally increase the efficacy of the partial agonist kainate (7,9) and fail to convert the competitive antagonist CNQX into a partial agonist (18,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TARPs regulate AMPA-R function by several mechanisms. They mediate the efficient cell surface expression of AMPA-Rs, modulate gating, affect agonist efficacy, and even attenuate intracellular polyamine block of calciumpermeable AMPA-Rs (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The effect of stargazin (γ-2) and other TARPs on GluA1 is not neuron specific and can be accurately mimicked in nonneuronal mammalian cells (18,(23)(24)(25), as well as Xenopus oocytes (13,14,17,26,27), suggesting that the basic mechanisms for TARP/AMPA-R interaction and TARPmediated regulation of AMPA-R trafficking are preserved in nonneuronal cells.…”
mentioning
confidence: 99%
“…Moreover, in the presence of TARPs, the AMPARs competitive antagonist 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX) acts as a partial agonist (Menuz et al, 2007). These results, together with the resolution of the crystal structure of CNQX bound to the TARP-less AMPAR LBD (Menuz et al, 2007), led the authors to propose a model where TARPs either strengthen the coupling between agonist-induced domain closure and channel opening, perhaps by promoting linker separation, or directly enhance the degree of domain closure induced by CNQX.…”
Section: Ampar Traffic Ampar Biosynthesis and Ampar Interaction Partnersmentioning
confidence: 99%